Case Report: Sapien 3 Transcatheter Heart Valve Embolization: Cause, Management, and Redo - Chen, Mi; Stähli, Barbara E.; Michel, Jonathan M.; Brinkert, Miriam; Tanner, Felix C.; Kasel, Albert Markus (Frontiers in Cardiovascular Medicine, 2021)
The transcatheter heart valve (THV) embolization is a rare but challenging complication in transcatheter aortic valve implantation (TAVI). We report the case of an 81-year-old man with Sapien 3 embolization caused by interrupted rapid pacing. In this setting, we describe the embolized THV management and the technique of the second Sapien 3 implantation.